Blood Transfusions, ENT Surgery, and Jehovah's Witnesses (International Journal of Food and Nutritional Sciences, 2022)
Blood transfusions are frequently necessary during otolaryngology surgical operations. Homologous blood transfusions pose dangers and may be unsuitable for certain patient populations. The Jehovah's Witnesses are well-known for their stance on blood products. The refusal of potentially lifesaving therapy presents treating professionals with ethical issues. Witnesses of Jehovah have battled globally for the freedom to refuse blood products. This article explores the need for blood in otolaryngological treatments, surgical measures to decrease blood loss, Jehovah's Witnesses' beliefs regarding the acceptance of blood, and the procedures and legal stances followed while treating Jehovah's Witnesses.